The Model of Corporate Culture in the Context of Strategic Initiatives of Machine-Building Enterprises (Economics and region, 2019)
The article presents new strategic initiatives for improving the efficiency of the machine-building enterprises, which are the basis for the strategic improvement of the overall efficiency of the machine-building enterprises, and the main ones of them are analytical procedures, the specific methods of which depend on the strategic and financial attractiveness of the industries developed by the enterprises. It is proved that managers should constantly study the corporate business portfolio and provide conclusions based on the single indicators: the number of enterprise divisions in attractive industries, the number of units in mature and stagnant industries; reduction of indicators that can negatively affect the overall productivity of the enterprise; the units dependence on factors of seasonality and periodicity, on the appearance of new technologies; the number of uncertain prospects; strategic match between the divisions of the enterprise; availability of portfolios of unnecessary units; resource matching between divisions. Managers have to carry out a qualitative analysis of the business portfolio, restructure the portfolio, and constantly review the resource allocation policy. It has been revealed that the analysis of strategic and financial attractiveness of corporate business portfolio should indicate whether the company is able to achieve the planned indicators in the current composition and resource base. Enterprise strategy changes are not required in case this analysis is confirmed. The measures to be taken in case of the threat of reduced efficiency have been developed. It has been established that in order the corporate culture at the machine-building enterprises were effective, it is necessary to implement the strategy of the machine-building enterprises, which consists of six strategy blocks. It has been established that in order for the proposed strategy to work at the machine-building enterprises, it must be in line with the principles of developing a successful strategy. As a result of the research, the principles of a successful strategy have been formulated.
Keywords: strategy; corporate culture; strategic initiatives; corporate culture model; corporate business portfolio